Improving thermal comfort conditions through the optimization of the self-product residential buildings envelope. Case of a region with a hot and arid climate: Biskra - Latreche, Sihem; Sriti, Leila (Journal of Applied Engineering Science & Technology; Vol 4 No 2 (2018): Issue In Progress, 2018)
To improve the thermal comfort conditions of the occupants in the individual housing and to reduce the energy consumption induced by the heating and cooling needs in the building, it is necessary to act on the main element which controls the heat exchanges with the environment: the envelope. This refers to the building’s outer skin that consisting of vertical opaque components (the walls ...), horizontal ones (roof ...) and various opening devices. The thermal performance of the envelope is mainly due to its geometrical and formal attributes, but the material characteristics of its components remain decisive for thermal exchanges with the environment. As part of the building at the interface of the indoor ambiances and the outdoor environment, the envelope is often the seat of a large number of heat exchange phenomena that affect not only the premises energy consumption but also the thermal comfort conditions of their occupants. This paper summarizes the main results obtained from an in-situ measurement campaign to evaluate the design parameters influencing the thermal comfort of self-produced individual housing relative to the hot and arid climate of Biskra. In addition, a thermal simulation carried out with the TYRNSYS 17 software has demonstrated the potential of improving the thermal comfort conditions of the self-produced individual housing thanks to adequate choices concerning the architectural and constructive attributes of the envelope.